2007
DOI: 10.1007/s00464-007-9578-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Nissen fundoplication in infants and children: analysis of 106 consecutive patients with special emphasis in neurologically impaired vs. neurologically normal patients

Abstract: The laparoscopic Nissen fundoplication can safely be performed with a low conversion rate and no surgical mortality in neurologically normal and neurologically impaired children. Neurologically impaired children are more susceptible to per- and postoperative complications. A good quality of life and a high index of satisfaction could be achieved in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 18 publications
(17 reference statements)
9
36
0
1
Order By: Relevance
“…This is consistent with the literature for neurologically impaired and healthy pediatric GERD patients [5,18,19]. A considerable discrepancy may exist between the evolution of objective data and subjectively experienced well-being [6][7][8].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the literature for neurologically impaired and healthy pediatric GERD patients [5,18,19]. A considerable discrepancy may exist between the evolution of objective data and subjectively experienced well-being [6][7][8].…”
Section: Discussionsupporting
confidence: 92%
“…The patients' time in hospital was comparable to that of other studies, ranging from 2.3 to 14.6 days. [16][17][18][19] We found it was difficult to accomplish the 360-degree fundoplication without dissociating the gastrosplenic ligament, especially in some children with a small gastric fundus. We also found that esophageal stenosis appeared more frequently in children who were treated with the Nissen-Rossetti procedure.…”
Section: Discussionmentioning
confidence: 96%
“…1 On the other hand, wrap migrations occurred more frequently in neurologically impaired children and those with postoperative esophageal atresia and diaphragmatic hernia. 1,35,36 In our series of 26 wrap migrations in neurologically normal children, there were 2 (7.7%) failures, but one had postoperative long-gap esophageal atresia and the other had tracheal stenosis (Table 2). Among the procedures, there was no difference in the ratio of redo surgery in neurologically normal children, 33 but the use of esophago-crural sutures and minimal esophageal dissection reduced the incidence of the postoperative transmigration of an LNF wrap.…”
Section: Recurrence Of Ger (Wrap Disruption) or Herniation Of The Wramentioning
confidence: 77%